Invited review: Small GTPases and their GAPs. Issue 8 (20th May 2016) - Mishra, Ashwini K.; Lambright, David G.
ABSTRACT: Widespread utilization of small GTPases as major regulatory hubs in many different biological systems derives from a conserved conformational switch mechanism that facilitates cycling between GTP‐bound active and GDP‐bound inactive states under control of guanine nucleotide exchange factors (GEFs) and GTPase activating proteins (GAPs), which accelerate slow intrinsic rates of activation by nucleotide exchange and deactivation by GTP hydrolysis, respectively. Here we review developments leading to current understanding of intrinsic and GAP catalyzed GTP hydrolytic reactions in small GTPases from structural, molecular and chemical mechanistic perspectives. Despite the apparent simplicity of the GTPase cycle, the structural bases underlying the hallmark hydrolytic reaction and catalytic acceleration by GAPs are considerably more diverse than originally anticipated. Even the most fundamental aspects of the reaction mechanism have been challenging to decipher. Through a combination of experimental and in silico approaches, the outlines of a consensus view have begun to emerge for the best studied paradigms. Nevertheless, recent observations indicate that there is still much to be learned. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 431–448, 2016.